Living with tension : pursuing ecological practice in an Aotearoa/New Zealand eco-village : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology at Massey University, Manawatu, New Zealand - Williams, Fraser (Massey University, 2017)
This research explores the experiences of an eco-village in Aotearoa/New Zealand, called Whakatipu, as they pursued ecologically ethical lifestyles. I stayed in Whakatipu and undertook participant observation for a month, working alongside residents, and interviewed eighteen of the thirty-eight people who live there. I use Bourdieu’s theory of practice to analyse how eco-villagers pursued their ideals in practice, with the aim of ascertaining whether elements of their experience could help others, such as myself, pursue ecological living. A key concept from Bourdieu’s framework is habitus, which helps to describe the naturalized, strategic way-of-being in the world that eco-villagers had developed. My findings illustrate that despite having strong motivations for ecological living, and the economic capacity to embark on this project, eco-villagers were unable to achieve many of their ideals. A common statement was ‘sustainability is not possible.’ All eco-villagers faced challenges to their ability to achieve an ecological lifestyle, and had to make compromises. Different people made different compromises, which contributed to conflict. Such challenges existed, in part, because the societal context that Whakatipu was embedded in was characterized by a consumer-capitalist ideology that eco-villagers simultaneously rejected, but remained reliant on. Rather than considering themselves to have failed, eco-villagers developed a habitus that enabled them to move towards their ideal ecological lifestyle, despite their inability to completely achieve this lifestyle. These experiences demonstrate the need for context to be considered in discussing the efforts of individuals to put their values into action. Ecologically ethical living cannot simply be the result of individual action and responsibility. Furthermore, rigid conceptions of ethical ‘success’ or ‘failure’ do not account for the attempts of individuals, with diverse backgrounds and worldviews, to lead better lives in constrained circumstances. Ecologically ethical living at an individual level is not simply a matter of failure or success, but is better understood as efforts that create progress towards an ideal.
Keywords: Environmentalism; Collective settlements; Village communities; Social aspects; New Zealand; Eco-village; Intentional community; Ecological ethics; Bourdieu; Eco-habitus; Ethical practice; Sustainability; Permaculture; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Social anthropology/ethnography::Social anthropology